Systemic antibodies administered by passive immunization prevent generalization of the infection by foot-and-mouth disease virus in cattle after oronasal challenge - Barrionuevo, Florencia Mariel; Di Giacomo, Sebastián; Bucafusco, Danilo; Ayude, Andrea Fabiana; Schammas, Juan Manuel; Miraglia, María Cruz; Capozzo, Alejandra Victoria; Borca, Manuel Victor; Perez Filgueira, Daniel Mariano (2018)
The role of passively transferred sera in the protection against aerogenous foot-and-mouth disease (FMD) virus infection in cattle was evaluated using vaccine-induced immune serum preparations obtained at 7 and 26 days post-vaccination (dpv). We showed that circulating antibodies were sufficient to prevent disease generalization after oronasal infection in animals passively transferred with 26-dpv serum but not with the 7-dpv serum. Conversely, conventional FMD vaccination provided clinical protection at 7 dpv, promoting fast and robust antibody responses upon challenge and even though antibody titers were similar to those found in animals passively immunized with 7-dpv serum. These results demonstrate that presence of antigen-specific antibodies is critical to prevent the dissemination of the virus within the animal. Conventional FMD vaccination additionally promoted the deployment of rapid, high titer and isotype-switched antibody responses at systemic and mucosal levels after infection, thus conferring protection even in the presence of low pre-challenge antibody titers.